Diurnal-activity Patterns of the Small Bee-eater (Merops orientalis) in Southern India - Abdul Hameed Mohamed Samsoor Ali; Subramanian Asokan (Tropical Life Sciences Research, 2015)
The diurnal time-activity patterns of the Small Bee-eater (Merops orientalis) were studied between 2005 and 2006 in the Nagapattinam District of Southern India. Bee-eaters were observed to spend an average of 52.5% of their day time scanning, 21.3% feeding, 13.3% flying, 8.8% resting and 4.1% engaging in preening activities. The time spent on scanning varied among seasons in 2005 (p<0.05) and among time blocks (p<0.05), but it did not vary among years or habitats (p>0.05). The feeding patterns differed among years, seasons within years, time blocks and habitats (p<0.05). The flying habits varied among years, time blocks and habitats (p<0.05) but did not change between seasons within years (p>0.05). The resting habits differed among years and habitats (p<0.05) but did not differ among seasons within years or time blocks (p>0.05). Preening differed among years and time blocks (p<0.05) but did not vary among seasons within years or habitats (p>0.05). We conclude that several factors, such as food availability, environmental factors and predation threats, may affect the diurnal activity patterns of Bee-eaters between habitats and seasons; a further study could clarify this conclusion. Corak diurnal masa-aktiviti oleh burung Small Bee-eater (Merops orientalis) telah dikaji antara tahun 2005 hingga 2006 di daerah Nagapattinam di Selatan India. Burung Bee-eaters telah diperhatikan menggunakan secara puratanya sebanyak 52.2% daripada masa mereka untuk mengimbas, 21.3% untuk makan, 13.3% untuk terbang, 8.8% untuk berehat dan 4.1% untuk aktiviti menyelisik. Masa yang telah digunakan untuk mengimbas berbeza mengikut musim pada tahun 2005 (p<0.05) dan antara blok masa (p<0.05), tetapi tidak berbeza antara tahun dan habitat (p>0.05). Corak pemakanan berbeza antara tahun, musim antara tahun, blok masa dan habitat (p<0.05). Pola penerbangan berbeza antara tahun, blok masa dan habitat (p<0.05) tetapi tidak berubah antara musim dalam tahun (p>0.05). Pola berehat berbeza antara tahun dan habitat (p<0.05) tetapi tidak berbeza antara musim dalam tahun atau blok masa (p>0.05). Aktiviti menyelisik berbeza antara tahun dan blok masa (p<0.05) tetapi tidak berbeza antara musim dalam tahun atau habitat (p>0.05). Kami membuat kesimpulan bahawa beberapa faktor, seperti ketersediaan makanan, faktor persekitaran dan ancaman pemangsa, boleh memberi kesan terhadap corak aktiviti diurnal burung Bee-eaters antara habitat dan musim; kajian lanjut boleh menjernihkan kesimpulan ini.